Lysimeter experiments of landfill liner enhanced with magnesium oxide - Kawther.Y.H. Al-Soudany; Mohammed Y. Fattah; Falah H. Rahil (Results in Engineering, 2025)
Lysimeters are frequently employed to replicate environmental conditions in landfill scenarios due to their relatively economical nature and brief study duration. Lysimeters frequently exhibit varying geometrical characteristics that modify the physical and thermodynamic attributes, potentially influencing waste material's decomposition rate and leaching dynamics. Based on the results of the lysimeter tests, lysimeters effectively evaluate and predict the impact of magnesium oxide (Mgo), a material suitable for constructing landfill liners. The findings substantiate that lysimeter investigations can significantly contribute to landfill engineering by identifying optimal strategies for waste containment and selecting appropriate materials for fabricating landfill barriers. Throughout the experimental procedure, the lysimeter was subjected to leachate application. In each hour of the experiment, the quantities of moisture, electric conductivity value (EC), temperature, settlement, pressure reaching the liner, and the total volume and pH of the obtained effluents were measured each week. This research explores and analyzes the role of magnesium oxide (C-M) in reducing permeability and measuring the shear strength properties of the composite material by utilizing a triaxial test. The sensor results demonstrated that MgO-enhanced liners provided superior long-term performance compared to clay. EC sensors showed MgO liners had lower and more stable conductivity. Moisture content sensors indicated that MgO-treated soil maintained better moisture regulation, reducing leachate. LVDT sensors revealed that MgO liners had minimal settlement, while clay experienced greater and prolonged settlement. Temperature sensors confirmed MgO's consistent thermal stability. In contrast, pressure, Total Dissolved Solid (TDS), pH, and flow rate sensors highlighted MgO's better structural integrity, lower dissolved solids, and controlled permeability over time.